Effect of Cu-, Zn-containing complex based on a porous matrix on fibroblast proliferation, apoptosis, necrosis and nitric oxide production - A. P. Lykov; L. N. Rachkovskaya; O. V. Poveshchenko; E. E. Rachkovsky; A. Yu. Letyagin (Сибирский научный медицинский журнал, 2021)
A comparative study of the effect of a matrix based on porous aluminum oxide and a silicon organic polymer polydimethylsiloxane (PDMS) (А12O3@PDMS) and a matrix complex with copper and zinc sorbed on its surface (Cu@Zn- А12O3@PDMS) on the functional properties of fibroblasts has been carried out. Material and methods. The effect of the Cu@Zn- А12O3@PDMS complex and the matrix on the cell proliferative potential (MTT test), apoptosis, necrosis and the production of stable nitric oxide (NO) metabolites were studied in an in vitro experiment with a human embryo fibroblast cell line (HEF-15). Results. The compared samples of Cu@Zn-A12O3@PDMS and Al2O3@PDMS are similar in their physico-chemical properties. Study of HEF-15 functional potential indicates a higher level of cell proliferation and ability to produce NO after contact with the complex. There was no significant increase in apoptosis and necrosis of HEF-15 in the presence of samples of the complex and the carrier. Conclusion. The absence of a significant negative effect of the tested samples on the functional status of cells of the FEH-15 line (proliferation, apoptosis, necrosis, NO secretion) in vitro allows the use of the Cu@Zn-A12O3@PDMS complex for further analysis of its safety in experimental models of skin defects in animals.